2009
DOI: 10.1002/cncr.24391
|View full text |Cite
|
Sign up to set email alerts
|

Health status and quality of life among non‐Hodgkin lymphoma survivors

Abstract: BACKGROUND:A growing body of evidence suggests that long‐term survivors with 1 of the more common forms of adult cancer report a quality of life (QOL) similar to that in the general population. However, specific concerns have been identified (sexual dysfunction, fatigue, distress) in this population. Also, less is known concerning survivors of adult non‐Hodgkin lymphoma (NHL), a disease often marked by alternating periods of disease and remission. Therefore, in the current study, the authors compared the QOL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
99
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 23 publications
5
99
0
1
Order By: Relevance
“…20 This suggests that there is no improvement in time, which is also shown by our 1-year follow-up results.…”
supporting
confidence: 70%
See 3 more Smart Citations
“…20 This suggests that there is no improvement in time, which is also shown by our 1-year follow-up results.…”
supporting
confidence: 70%
“…One prospective and three cross-sectional studies also observed clinically worse scores for HRQOL domains for NHL survivors compared with those of a normative population. 13,15,17,20 Numerous patients in our study showed large improvements (19-23%) or deteriorations (22-28%) within 1 year, which both indicate a clinically relevant change. 31 However, it is too soon to determine whether this can be defined as an actual change, due to regression to the mean.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…19,20 A better understanding of patients' longitudinal experiences means we can more effectively target interventions. By combining patient-reported data with other information in the electronic health record, such as laboratory findings and clinical assessments, we paint a more detailed picture of the patient and his or her experiences, better heralding the future and preparing clinicians to more expertly manage the impact of hematologic malignancies and their treatments over time.…”
mentioning
confidence: 99%